Cognitive reappraisal and expressive suppression strategies role in the emotion regulation: an overview on their modulatory effects and neural correlates - Cutuli, Debora (Frontiers in Systems Neuroscience, 2014)
Individuals regulate their emotions in a wide variety of ways. In the present review it has been addressed the issue of whether some forms of emotion regulation are healthier than others by focusing on two commonly used emotion regulation strategies: cognitive reappraisal (changing the way one thinks about potentially emotion-eliciting events) and expressive suppression (changing the way one behaviorally responds to emotion-eliciting events). In the first section, experimental findings showing that cognitive reappraisal has a healthier profile of short-term affective, cognitive, and social consequences than expressive suppression are briefly reported. In the second section, individual-difference findings are reviewed showing that using cognitive reappraisal to regulate emotions is associated with healthier patterns of affect, social functioning, and well-being than is using expressive suppression. Finally, brain structural basis and functional activation linked to the habitual usage of cognitive reappraisal and expressive suppression are discussed in detail.